(untitled) (World Economics and Finance Bulletin, 2022)
The research aims to indicate the role that tax revenues can play in financing the fiscal deficit in the general budget, by standing on the volume of tax revenues collected as well as identifying the sources of public revenues and their importance in achieving this goal. The research was applied in the Iraqi General Commission for Taxes for the year data Finance 2021 to show the role of tax revenues in financing the Iraqi state budget, By determining the proportion of tax revenues to the total public revenues of the state and its contribution to bridging expenditures, the research reached a set of conclusions, the most important of which was the dependence of the Iraqi state in its financial resources on oil revenues with a large part in financing public spending, and tax revenues also made important achievements in financing the budget Public amounts after oil revenues to fill part of the financial deficit in the budget and help in the advancement of the economic and financial reality of the state.